2022
DOI: 10.3389/fnut.2022.857698
|View full text |Cite
|
Sign up to set email alerts
|

Macrominerals and Trace Minerals in Commercial Infant Formulas Marketed in Brazil: Compliance With Established Minimum and Maximum Requirements, Label Statements, and Estimated Daily Intake

Abstract: Infant formulas are the main nutritional source for infants when breastfeeding is not possible or recommended. The daily need for specific nutrients, such as essential minerals, in early stages of a child's life is high because of rapid infant growth and development, which impose metabolic flux increases on these pathways to support growth, physical activity, and defense against infections. In this context, this research aimed to determine macromineral and trace mineral contents in starting (phase 1) and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Correlating the findings in this study with those found in previous works, in which the objective was to evaluate the contents of essential minerals in the same infant formula samples and with the same analysis methodology, we observed that, in general, the concentrations found for essential minerals were significantly higher than those observed for toxic elements [ 15 ]. However, it is worth noting that it is not possible to directly correlate the metabolic interference of non-essential metals with essential minerals since the analysis was performed directly on the product and not after its ingestion.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Correlating the findings in this study with those found in previous works, in which the objective was to evaluate the contents of essential minerals in the same infant formula samples and with the same analysis methodology, we observed that, in general, the concentrations found for essential minerals were significantly higher than those observed for toxic elements [ 15 ]. However, it is worth noting that it is not possible to directly correlate the metabolic interference of non-essential metals with essential minerals since the analysis was performed directly on the product and not after its ingestion.…”
Section: Resultssupporting
confidence: 81%
“…Metals and metalloids were determined according to the US EPA method 6020B [ 14 ] by inductively coupled plasma mass spectrometry (ICP-MS), with some modifications, as performed in previous studies by the same authors [ 15 ]. Briefly, 100 mg of each sample were mixed with 1 mL of concentrated sub-boiled distilled nitric acid and left overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Essential mineral concentrations (Na, K, Mg, Mn, P and Zn) were determined according to Almeida et al [ 10 , 34 ] by inductively sequential coupled plasma optical emission spectrometry (ICP-OES) with a radial view on a Horiba Jobin Yvo Ultima 2 ICP-OES (Longjumeau, FRA), equipped with a cyclonic nebulization chamber, MiraMist type nebulizer (Mira Mist CE, Burgener Research Inc., Mississauga, ON, CAN) and automatic AS 421 sampler model. Instrumental ICP-OES conditions are included in the Supplementary file—Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Red beetroots are also rich in mineral salts that contribute to the proper functioning of the body, as components in the formation and maintenance of bones in the human body, as cofactors or regulators of enzymatic reactions, acting in the conduction of nerve impulses, coagulation, the maintenance of osmotic balance, the transfer of substances through membranes and in the process of cellular respiration. The lack of mineral salts in the body of living beings can be fatal, as it significantly alters metabolism [ 10 ]. Furthermore, strong evidence suggests that the consumption of red beetroot, one of the most important sources of dietary NO 3 − , improves vascular function by converting NO 3 − to NO [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trace and mineral elements in the body have different functions in the framework of enzymes and proteins that maintain homeostasis, so their content should be controlled in infant nutrition, in addition to the fact that these elements can affect the osmolality of the ingested food. Trace element requirements are critical during infancy and early childhood due to the very high growth rate of children, and insufficient mineral intake can lead to deficiencies that can impair body function [10,11].…”
Section: Introductionmentioning
confidence: 99%